Video-Analysis of Conflict Situations on Selected Roundabouts in the Czech Republic - Vladislav Krivda (Communications - Scientific letters of the University of Zilina, 2011)
The paper deals with video-analysis of conflict situations in road traffic and presents results of researches which were performed on selected roundabouts in the Czech Republic. This article refers to suitability of usage video-recording to analysis of behavior of participants of road traffic and also to monitoring of the danger places on the roundabouts. There are results of analyses which were performed in 2010 and also comparative analysis of conflict situations and possible traffic accidents.